Incremental clinical and economic burden of suspected respiratory infections due to multi-drug-resistant Pseudomonas aeruginosa in the United States. Issue 2 (October 2019) - Tabak, Y.P.; Merchant, S.; Ye, G.; Vankeepuram, L.; Gupta, V.; Kurtz, S.G.; Puzniak, L.A.
Summary: Background: Multi-drug resistant (MDR) Pseudomonas aeruginosa can negatively affect patients and hospitals. Aim: To evaluate excess mortality and cost burden among patients hospitalized with suspected respiratory infections due to MDR P. aeruginosa vs patients with non-MDR P. aeruginosa in 78 United States (US) hospitals . Methods: This study analyzed electronically captured microbiological and outcomes data of patients hospitalized with non-duplicate P. aeruginosa isolates from respiratory sources collected ≥3 days after admission to identify hospital-onset MDR or non-MDR P. aeruginosa per the Centers for Disease Control and Prevention definition. The risk of multi-drug resistance was estimated on mortality, length of stay (LOS), cost, operation gain/loss, and 30-day readmission. A sensitivity analysis was conducted utilizing a cohort with pharmacy data available. Findings: Of 523 MDR and 1381 non-MDR P. aeruginosa cases, unadjusted mortality was 23.7% vs 18.0% and multi-variable-adjusted mortality was 20.0% (95% confidence interval (CI): 14.3–27.2%) vs 15.5% (95% CI: 11.2–20.9%; P =0.026), the average adjusted excess LOS was 6.7 days ( P <0.001); excess cost per case was US$22, 370 higher ( P =0.002) and operational loss per case was US$10, 661 ( P =0.024) greater, and the multi-variable adjusted readmission rate was 16.2% (95% CI: 11.2–22.9%) vs 11.1% (95% CI: 7.8–15.6%; P =0.006). The sensitivity analysis yielded similar results. Conclusions: Compared with suspected infections due to non-MDR P. aeruginosa, patients with MDR P. aeruginosa had higher risk of mortality, readmission, and longer LOS, as well as US$20, 000 incremental cost and >US$10, 000 incremental net loss per case after controlling for patient and hospital characteristics.